2012
DOI: 10.1186/1471-2482-12-5
|View full text |Cite
|
Sign up to set email alerts
|

SUBMIT: Systemic therapy with or without up front surgery of the primary tumor in breast cancer patients with distant metastases at initial presentation

Abstract: BackgroundFive percent of all patients with breast cancer have distant metastatic disease at initial presentation. Because metastatic breast cancer is considered to be an incurable disease, it is generally treated with a palliative intent. Recent non-randomized studies have demonstrated that (complete) resection of the primary tumor is associated with a significant improvement of the survival of patients with primary metastatic breast cancer. However, other studies have suggested that the claimed survival bene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
21
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 21 publications
0
21
0
Order By: Relevance
“…33 However, as all the included studies were retrospective, and based on this, one cannot conclude that surgical removal of the primary breast tumor improves overall survival. Therefore, several randomized controlled trials were designed to determine if local therapy would improve survival in a randomized fashion in patients with de novo metastatic breast cancer (Table 2) 34,35 In the last couple of years, presented but unpublished results from two of these randomized controlled trials did not confirm the favorable role of primary surgery for all the patients with de novo metastatic breast cancer that was previously suggested by most retrospective studies. In the study from the Turkish Federation of Societies for Breast Diseases Soran et al, suggested that patients with isolated bone metastases may benefit from surgery, whereas such an approach was even detrimental in patients with visceral involvement.…”
Section: Reviewmentioning
confidence: 97%
“…33 However, as all the included studies were retrospective, and based on this, one cannot conclude that surgical removal of the primary breast tumor improves overall survival. Therefore, several randomized controlled trials were designed to determine if local therapy would improve survival in a randomized fashion in patients with de novo metastatic breast cancer (Table 2) 34,35 In the last couple of years, presented but unpublished results from two of these randomized controlled trials did not confirm the favorable role of primary surgery for all the patients with de novo metastatic breast cancer that was previously suggested by most retrospective studies. In the study from the Turkish Federation of Societies for Breast Diseases Soran et al, suggested that patients with isolated bone metastases may benefit from surgery, whereas such an approach was even detrimental in patients with visceral involvement.…”
Section: Reviewmentioning
confidence: 97%
“…Since 2011 several randomized trials have started accrual comparing loco-regional treatment of primary vs. no treatment in stage IV patients at presentation [124,125].…”
Section: B 100% (24) Yes 0% (0) Abstain (24 Voters)mentioning
confidence: 99%
“…One ongoing trial may answer some of these questions. It is randomised cohort trial comparing immediate resection of the primary tumour, followed by systemic therapy and systemic therapy, followed by delayed surgical resection (24). It is prudent to revise this meta-analysis when the results of this and other similar trials become available.…”
Section: Discussionmentioning
confidence: 99%